Rhizoma Paridis saponins suppresses vasculogenic mimicry formation and metastasis in osteosarcoma through regulating miR-520d-3p/MIG-7 axis - Nan Yao; Jing Zhou; Yantao Jiang; Qiaomei Jin; He Zhu; Jian Zhang; Zhenlin Li (Elsevier, 2022)
Osteosarcoma (OS) is a highly metastatic bone cancer that usually affects children. Rhizoma Paridis saponins (RPS) have been identified to show a broad-spectrum anti-tumor activity. Our previous study has identified vasculogenic mimicry (VM) as an indicator of poor prognosis for OS. Rhizoma Paridis ethanol extract exhibits potent anti-OS property. However, the anti-metastatic effect of RPS on OS and the detailed mechanisms remain unknown. RPS was characterized by liquid chromatography/quadrupole time-of-flight mass spectrometry (LC/Q-TOF/MS) analysis. The anti-OS, anti-metastasis and anti-VM activities of RPS were investigated using in vitro biological assays and a xenograft mouse model. Western blot, qRT-PCR, ELISA, Phalloidin staining and immunohistochemistry assays were conducted to investigate the molecular mechanism of RPS. A total of 34 phytochemicals from RPS were identified by LC/Q-TOF/MS. RPS dose-dependently suppressed the OS cell proliferation, metastasis and VM formation in vitro and in vivo. Mechanically, we found that RPS downregulated migration-inducing gene 7 (MIG-7) expression, resulting in inhibition of the PI3K/MMPs/Ln-5γ2 pathway and cell protrusion formation. Additionally, we confirmed that RPS downregulated MIG-7 by upregulating miR-520d-3p expression. Our results suggests that RPS inhibits the VM formation and metastasis of OS by modulating the miR-520d-3p/MIG-7 signaling axis.